Ambition Meets Reality: Achieving GHG Emission Reduction Targets in the Livestock Sector of Latin America - Arango, Jacobo; Ruden, Alejandro; Martínez Barón, Deissy; Loboguerrero Rodriguez, Ana María; Berndt, Alexandre; Chacón, Mauricio; Torres, Carlos Felipe; Oyhantçabal, Walter; Gómez, Carlos A.; Ricci, Patricia; Ku-Vera, Juan Carlos; Burkart, Stefan; et al. (Frontiers Media, 2020)
Livestock production is a very relevant source of income and agricultural greenhouse gas (GHG) emissions in Colombia, Brazil, Argentina, Costa Rica, Uruguay, Mexico, and Peru. Several management and technological options with enteric methane mitigation potential have been evaluated and their scaling is anticipated to contribute toward achieving GHG emission reduction targets in the framework of the Paris Agreement. Yet, widespread adoption of promising mitigation options remains limited, raising questions as to whether envisaged emission reduction targets are achievable. Using findings from local studies, we explore the mitigation potentials of technologies and management practices currently proposed to mitigate enteric methane emissions from cattle production systems in the higher emitting countries of Latin America. We then discuss barriers for adopting innovations that significantly reduce cattle-based enteric methane emissions and the major shifts in policy and practice that are needed to raise national ambitions in the high emitting countries. Using the latest science and current thinking, we provide our perspective on an inclusive approach and re-imagine how the academic, research, business and public policy sectors can support and incentivize the changes needed to raise the level of ambition and achieve sustainable development goals (SDG), considering actions from the farm to the national scale.